1986
DOI: 10.1577/1548-8659(1986)6<129:poripa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Rotenone in Ponds at Different Temperatures

Abstract: Two ponds were treated with liquid rotenone (5% rotenone), one with 3 mg/L at 24°C and the other with 2 mg/L at 0°C (concentrations of active rotenone were 0.15 and 0.10 mg/L, respectively). Water samples were collected and analyzed by high‐performance liquid chromatography. The concentration of rotenone declined to 0.02 mg/L in 48 h in warm water and in 11 d in cold water. The half‐life of rotenone was calculated at 13.9 h in warm water and 83.9 h in cold water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…They are broadly similar to those reported overseas (e.g. Gilderhus et al, 1986Gilderhus et al, , 1988Vasquez et al, 2012), with the half-life being in the order of days and complete dissipation occurring within two months.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…They are broadly similar to those reported overseas (e.g. Gilderhus et al, 1986Gilderhus et al, , 1988Vasquez et al, 2012), with the half-life being in the order of days and complete dissipation occurring within two months.…”
Section: Discussionsupporting
confidence: 90%
“…The environmental fate of pesticides is of concern to regulatory authorities and the public, and if pest control tools are to be maintained they must be shown to have minimal long term impacts on the environment. Therefore, information about the half-life of rotenone is valuable when applying for approval to use it from consenting authorities (Dawson et al, 1991;Finlayson et al, 2014) and designing water sampling protocols (Gilderhus et al, 1986(Gilderhus et al, , 1988Finlayson et al, 2014). It is also important in determining the correct amount of rotenone to apply and for maintaining public confidence in the use of rotenone by showing that it does not persist in the environment (Finlayson et al, 2001Vasquez et al, 2012).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not known whether rotenone is metabolised by aquatic vegetation. Gilderhus et al (1986Gilderhus et al ( , 1988 examined the fate of rotenone in shallow ponds at differing temperatures and found that rotenone loss was ten times faster at 23 o C than at 1 o C. The half-life of rotenone in natural waters above 20 o C is generally less than one day. Gilderhus (1982) and Dawson et al (1991) showed that the rapid loss of rotenone in treated ponds was not solely attributable to chemical decay.…”
Section: E N V I R O N M E N T a L P E R S I S T E N C Ementioning
confidence: 99%